2005
DOI: 10.1038/sj.jea.7500430
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective assessment of exposure to traffic air pollution using the ExTra index in the VESTA French epidemiological study

Abstract: This study applies a traffic exhaust air dispersion model (the ExTra index) to 403 children enrolled in a French multicentric case-control study, the VESTA study (Five [V] Epidemiological Studies on Transport and Asthma). The ExTra index (previously validated by our team) was used to assess lifelong average traffic-related air pollutant (TAP) concentrations (nitrogen oxides) children in the study were exposed to in front of their living places. ExTra index took into account traffic density, topographical para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…We expected obstruction to modify PM or EC, in keeping with recent findings suggesting that roadside barriers reduce PM concentrations [ 32 ]. Though we did not expect to find this effect for a gaseous pollutant such as NO 2 , this result is supported by recent evidence that residential NO 2 concentrations differed significantly depending on whether the home faced onto the courtyard or street, after accounting for distance to road [ 33 ]. Our findings may also be in part related to our passive sampling approach (as an obstruction could reduce the face velocity on the sampler).…”
Section: Discussionsupporting
confidence: 69%
“…We expected obstruction to modify PM or EC, in keeping with recent findings suggesting that roadside barriers reduce PM concentrations [ 32 ]. Though we did not expect to find this effect for a gaseous pollutant such as NO 2 , this result is supported by recent evidence that residential NO 2 concentrations differed significantly depending on whether the home faced onto the courtyard or street, after accounting for distance to road [ 33 ]. Our findings may also be in part related to our passive sampling approach (as an obstruction could reduce the face velocity on the sampler).…”
Section: Discussionsupporting
confidence: 69%
“…Similar results were obtained in a French study in which topographic and traffic characteristics of residences and nurseries/schools were found to be similar. 45 Furthermore, air pollution levels at the home address are highly relevant as exposure estimates in infancy because in Sweden children usually do not start day care before 12 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Although we conducted several sensitivity analyses to reduce potential moving-related exposure misclassification and noted no changes in the results, it is possible that some exposure misclassification remains, especially at the older ages when children spend a larger proportion of their time at school. However, a Swedish and French study showed that exposures from traffic assessed at the home address are good approximations of those at schools, possibly because schools tend to be located in the close vicinity of homes ( Gruzieva et al, 2012 ; Reungoat et al, 2005 ). Additionally, a study conducted in the United States found little differences between time-weighted averages of diesel exposures estimated at all addresses where a child spent more than eight hours per week and those estimated only at the home address ( Ryan et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%